2008
DOI: 10.1242/dev.025767
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a regulates directional cell migration and cell proliferation via Ror2-mediated noncanonical pathway in mammalian palate development

Abstract: Tissue and molecular heterogeneities are present in the developing secondary palate along the anteroposterior (AP) axis in mice. Here, we show that Wnt5a and its receptor Ror2 are expressed in a graded manner along the AP axis of the palate. Wnt5a deficiency leads to a complete cleft of the secondary palate, which exhibits distinct phenotypic alterations at histological, cellular and molecular levels in the anterior and posterior regions of the palate. We demonstrate that there is directional cell migration wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
298
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(315 citation statements)
references
References 53 publications
15
298
1
1
Order By: Relevance
“…In addition, it has recently been reported that Wnt5a regulates cell polarity in cooperation with Par/Atypical protein kinase C pathway (Schlessinger et al, 2007), and that Ror2 mediates Wnt5a-induced polarized cell migration by activating JNK through its association with filamin A (Nomachi et al, 2008). The role of Wnt5a/Ror2 signaling in polarized cell migration has been further confirmed within the developing palate using in vitro organ culture assays (He et al, 2008). Despite the accumulating evidence showing the crucial roles of Wnt5a/Ror2 signaling in polarized cell migration, it remains unknown whether or not Wnt5a/Ror2 signaling is involved in the tumor-cell motility and invasiveness.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, it has recently been reported that Wnt5a regulates cell polarity in cooperation with Par/Atypical protein kinase C pathway (Schlessinger et al, 2007), and that Ror2 mediates Wnt5a-induced polarized cell migration by activating JNK through its association with filamin A (Nomachi et al, 2008). The role of Wnt5a/Ror2 signaling in polarized cell migration has been further confirmed within the developing palate using in vitro organ culture assays (He et al, 2008). Despite the accumulating evidence showing the crucial roles of Wnt5a/Ror2 signaling in polarized cell migration, it remains unknown whether or not Wnt5a/Ror2 signaling is involved in the tumor-cell motility and invasiveness.…”
Section: Introductionmentioning
confidence: 83%
“…2B). The delay of shelf extension affected the anterior and posterior halves equally in the affected genotypes, unlike in several other cleft palate mutants (He et al, 2008;Yu et al, 2005;Zhang et al, 2002). Palatal extension to the midline was delayed to a greater extent in bt/bt than in Adamts9 +/-;bt/+ mice ( Fig.…”
Section: Independent Contributions Of Adamts9 and Adamts20 To Mouse Pmentioning
confidence: 96%
“…Several Wnts have been implicated in palate closure: palate clefting is observed with full penetrance in Wnt5a -/-mice (He et al, 2008) and with partial penetrance in Wnt9b -/-mice (Juriloff et al, 2006); WNT3 mutations have been identified in a human syndrome that includes cleft palate (Niemann et al, 2004), and mouse palate explant experiments suggest that Wnt11 functions in the terminal fusion process (Lee et al, 2008). To examine potential Wnt/frizzled interactions in the palate, we used RT-PCR to survey E13 palates for the presence of transcripts coding for each of the 19 mammalian Wnt proteins (see Fig.…”
Section: Fully Penetrant Palate Clefting In Fz1mentioning
confidence: 99%